INTELLIGENT LPG GAS LEAK DETECTION TOOL WITH SMS NOTIFICATION - Hasibuan, Muhammad Siddik (Jurnal Informatika, 2019)
Gas is a molecule that is not bound, formless, invisible and can turn into search or solid at certain temperature pressures. LPG gas is one of the needs for industry and household needs, namely for cooking. LPG gas in Indonesia is the cause of many fires, a factor that often causes LPG gas fires is a damaged gas regulator. Therefore prevention and security are needed to minimize fires. Seeing this and given the technological developments, an intelligent Arduino-based device was created that was able to overcome this problem. This tool is equipped with MQ-2, SIM800L, and buzzer gas sensors. In an embedded device the system that can convert input data received from the sensor Mq-2 sensor works to detect propane and butane gas, then the system will send the actual data in the form of short messages (SMS) to the mobile number that has been registered into the system. Besides being able to send SMS the system also emits a sound that is generated from the buzzer